Trends in hospitalization of patients with Acute Heart Failure (Research, Society and Development, 2020)
Objective: Identify the causes of decompensation and trends in the classification and treatment of hospitalized patients with heart failure. Methods: Observational study, carried out in a private cardiology reference hospital in the city of Aracaju / SE. Medical records from June 2015 to August 2018 were analyzed and questionnaires were applied to patients over 18 years old, who presented with acute form or acute exacerbation of chronic Heart Failure. Results: 180 patients were included, with a mean of 73 years and a male prevalence (52.2%). It was identified that 94.4% of the patients had dyspnea, 86.1% had a history of systemic arterial hypertension, arrhythmia (33.3%) was the main cause of decompensation and the hypertensive etiology was recognized in 39.4% of the cases. Heart Failure with reduced ejection fraction was identified in 50.7%, with a greater tendency in males (p